The Effect of Background Music on Inhibitory Functions: An ERP Study - Burkhard, Anja; Elmer, Stefan; Kara, Denis; Brauchli, Christian; Jäncke, Lutz (Frontiers in Human Neuroscience, 2018)
The influence of background music on cognitive functions is still a matter of debate. In this study, we investigated the influence of background music on executive functions (particularly on inhibitory functions). Participants completed a standardized cued Go/NoGo task during three different conditions while an EEG was recorded (1: with no background music, 2: with relaxing or 3: with exciting background music). In addition, we collected reaction times, omissions, and commissions in response to the Go and NoGo stimuli. From the EEG data, event-related potentials (ERPs) were calculated for the Go and NoGo trials. From these ERPs, the N2 and P3 components were specifically analyzed since previous studies have shown that these components (and particularly the Go-NoGo difference waves) are strongly associated with inhibitory functions. The N2 and P3 components of the difference waves (N2d and P3d) were used for statistical analyses. The statistical analyses revealed no differences between the three conditions in terms of amplitudes and latencies of the N2d and P3d components. In addition, reaction times, omissions, and commissions were comparable across all conditions. Our results suggest that in the context of this paradigm, music as background acoustic stimulation has no detrimental effects on the performance of a Go/NoGo task and neural underpinnings.